2012
DOI: 10.1186/1471-2105-13-224
|View full text |Cite
|
Sign up to set email alerts
|

Improved model quality assessment using ProQ2

Abstract: BackgroundEmploying methods to assess the quality of modeled protein structures is now standard practice in bioinformatics. In a broad sense, the techniques can be divided into methods relying on consensus prediction on the one hand, and single-model methods on the other. Consensus methods frequently perform very well when there is a clear consensus, but this is not always the case. In particular, they frequently fail in selecting the best possible model in the hard cases (lacking consensus) or in the easy cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
224
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(228 citation statements)
references
References 41 publications
1
224
1
2
Order By: Relevance
“…Phyre2 (Kelley et al, 2015) was used to model protein structures based on these sequences based on solved protein structures with highest percentage amino acid sequence identity. The quality of the models at the global (full protein) and local (F 420 -binding site) scales were assessed using ProQ2 (Ray et al, 2012). F 420 -binding motifs were identified based on previous studies (Eguchi et al, 1984;Purwantini and Daniels, 1998;Aufhammer et al, 2004;Ahmed et al, 2015).…”
Section: Evolutionary Analysismentioning
confidence: 99%
“…Phyre2 (Kelley et al, 2015) was used to model protein structures based on these sequences based on solved protein structures with highest percentage amino acid sequence identity. The quality of the models at the global (full protein) and local (F 420 -binding site) scales were assessed using ProQ2 (Ray et al, 2012). F 420 -binding motifs were identified based on previous studies (Eguchi et al, 1984;Purwantini and Daniels, 1998;Aufhammer et al, 2004;Ahmed et al, 2015).…”
Section: Evolutionary Analysismentioning
confidence: 99%
“…Nowadays, the tools, like QMEAN server, one of the most efficient tool available for assessing the accuracy of a structural model, are not appropriate to validate a transmembrane protein model (23). ProQM, the only tool available to assess membrane protein models, indicated that the quality of the model is medium (24). However, the present model provides useful information regarding helix spatial organization that should be further validated experimentally.…”
mentioning
confidence: 90%
“…ProQ2 (29) did not flag serious problems in the local or global quality of the homology models. Minor issues that were identified tended to occur in longer turns or loops.…”
Section: Methodsmentioning
confidence: 99%